Composition, structure, and management potential of secondary dry tropical vegetation in two abandoned henequen plantations of Yucatan, Mexico - Mizrahi, A.; Ramos Prado, J.M.; Jimenez-Osornio, J.
presenteda ndt heir managemenpto tentiald iscussedT.h e study was carriedo ut in the Haciendao f Kancabchen Yucatan, Mexico in 12- and2 6-year-olds econdaryfo rests.S peciesri chnessa ndd iversity were greatera st he standg rew older.E ven though 73
Keywords: DRY TROPICAL FOREST; SUCCESSION; MANAGEMENT POTENTIAL